Validación de los métodos físico-químicos para control de calidad de agua potable en el laboratorio de una empresa de bebidas gaseosas (2019)
The company that produces soft drinks requires the use of drinking water for the development of its products, which is why it has a water quality laboratory, where through analytical techniques it determines the parameters of Alkalinity, Conductivity, Hardness, pH, Total Dissolved Solids and Turbidity. That said, the physical-chemical methods were validated from the statistical analysis of linearity, limits of detection and quantification, precision and accuracy. The results obtained guaranteed the validity of the methods because the linearity was greater than 0.99, the accuracy in repeatability conditions was less than 7% and the Fisher factor was lower than the theoretical one by applying reproducibility factors and for accuracy they were reported values less than 15%.